PENERAPAN METODE APPLICATION DEVELOPMENT DALAM PERANCANGAN PROGRAM PENJUALAN TANAH KAVLING BERBASIS WEBSITE - Saputra, Maharrandi Dwiki; Solecha, Kusmayanti (INTI Nusa Mandiri, 2024)
Currently, property developer agencies are progressing rapidly, the supporting elements of home ownership are also facilitated by the presence of home ownership loans. In the process of selling land property, it still uses conventional methods so that customers must be present in person to find and order land plots. The sales process is still manual, causing errors in reporting and making it difficult for employees to find documents. The purpose of this research is to design a website-based land plot sales program that can facilitate the process of providing online land availability information, the land plot sales process which is equipped with a payment scheme calculator feature and a track booking feature. This research uses the Rapid application Development (RAD) model with the aim that the application can be efficient in processing time, and uses the black-box testing method in its testing. The result of this research is a land plot sales website with a payment scheme calculator feature and a track booking feature, so that the sales process becomes efficient, reporting data becomes accurate and data search becomes easier.